Reflections in comics: the views of queer artists in producing body image comics and how their work can improve health. Issue 5 (3rd September 2021) - Joy, Phillip; Gauvin, Stéphanie E. M.; Aston, Megan; Numer, Matthew
ABSTRACT: Comics are an innovative way to translate health knowledge and research to service providers and communities. A theoretical framework intertwining poststructuralism and queer theory was used to explore the experiences of queer artists in the creation and production of body image comic anthology entitled Rainbow Reflections: Body Image Comics for Queer Men. The aim was to examine the beliefs of the artists about the potentiality of comics to address body image concerns for queer men. Body image concerns may create negative health experiences, isolation, loneliness, and sexual intimacy concerns. Nineteen self-identifying queer artists participated in the study. Discourse analysis revealed five threads of discourse that bring understanding on how comics can improve body image, and the health and well-being of both the artists through the act of creation and the reader through the act of consumption. Theses threads of discourse include: 1) Creating a unique language, 2) Revealing and healing themselves, 3) Exploring cultural influences, 4) Expanding spaces for queer men and their bodies, and 5) Connecting men. The findings reveal that comics can create knowledge and stimulate discussions about body image and has the potential to positively influence the health of queer men.